2017
DOI: 10.1021/jacs.7b05125
|View full text |Cite
|
Sign up to set email alerts
|

A Chemoselective Rapid Azo-Coupling Reaction (CRACR) for Unclickable Bioconjugation

Abstract: Chemoselective modification of complex biomolecules has become a cornerstone of chemical biology. Despite the exciting developments of the past two decades, the demand for new chemoselective reactions with unique abilities, and those compatible with existing chemistries for concurrent multisite-directed labeling, remains high. Here we show that 5-hydroxyindoles exhibit remarkably high reactivity toward aromatic diazonium ions and this reaction can be used to chemoselectively label proteins. We have previously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
92
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(93 citation statements)
references
References 52 publications
1
92
0
Order By: Relevance
“…This had previously been reported by both our group and others to facilitate release of aryl diazonium for protein labeling via increasing the basicity of the compound. [9] We were relieved to find that the presence of a fluorophore in conjugation with the triazabutadiene did not prevent the photochemistry. Once more we utilized BSA as a model protein to show labeling could be attained at pH 7 by irradiation at 350 nm (Figure 1c).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This had previously been reported by both our group and others to facilitate release of aryl diazonium for protein labeling via increasing the basicity of the compound. [9] We were relieved to find that the presence of a fluorophore in conjugation with the triazabutadiene did not prevent the photochemistry. Once more we utilized BSA as a model protein to show labeling could be attained at pH 7 by irradiation at 350 nm (Figure 1c).…”
mentioning
confidence: 99%
“…This result is consistent with previous work on using light to release aryl diazonium ions from triazabutadienes. [9] …”
mentioning
confidence: 99%
“…Indeed, we have recently developed an oxidative coupling reaction that enables selective attachment of various aromatic amines to the 5HTP residue . Additionally, we have shown that various aryldiazonium ions react rapidly with the 5HTP residue, leading to the development of a chemoselectively rapid azo‐coupling reaction (CRACR) for site‐specific protein labeling …”
Section: Figurementioning
confidence: 76%
“…Although we have previously kinetically characterized the azo‐coupling reaction between free 5HTP and 4CDZ, it is presumable that the 5‐hydroxyindole residue on a protein may react somewhat differently. The quenchergenic aspect of CRACR described herein should enable facile measurement of the kinetics of this labeling reaction on sfGFP, by monitoring the concomitant decrease in its fluorescence.…”
Section: Figurementioning
confidence: 99%
“…Indeed, we have recently demonstrated that 5HTP undergoes azo-coupling reaction significantly faster than canonical amino acids (e.g., tyrosine), providing a basis for chemoselective protein labeling. [6] 5-hydroxyindoles such as serotonins are also known to be prone to oxidation under relatively mild conditions, producing oligomeric products. [7] This provides an opportunity to develop new chemoselective protein modification strategies targeted to 5HTP through oxidative coupling reactions (Figure 1).…”
mentioning
confidence: 99%